Exploring Public Attitudes to Welfare over the Longue Durée: Re‐examination of Survey Evidence from Beveridge, Beatlemania, Blair and Beyond. (November 2016) - Hudson, John; Lunt, Neil; Hamilton, Charlotte; Mackinder, Sophie; Meers, Jed; Swift, Chelsea
Abstract: It is commonly argued that public support for the welfare state is in long‐term decline in the UK. Evidence from the British Social Attitudes Survey (BSA) is typically cited to support this claim, but it only stretches back to 1983. Few would disagree that the Thatcher years offered an unusual socio‐political‐economic context, which raises a question over whether the BSA's early 1980s baseline provides a misleading view on support for the welfare state over the longue durée. In this article, we explore this issue, piecing together data from the Beveridge era through to the present day, drawing on data from contemporary studies and surveys; opinion polls; and historical government surveys and reports. Our method is undoubtedly a 'second best approach', making use of often limited historical data, which means we remain cautious in offering bold findings. However, we argue there is some evidence to suggest the 1980s were an unusual moment, suggesting the decline in support for welfare is less dramatic than analysis of the BSA might make it seem, but also that support for the welfare state during the postwar consensus years was likely more equivocal than we often believe it to be from today's perspective, perhaps reflecting a tendency to reify this period as a 'golden age' of welfare and so underplaying the complexity of the politics of social policy in the pre‐BSA period.